Social Entrepreneurship as Students’ Social Transformation in an Indonesian Islamic University - Thayib Thayib; Abdulloh Hamid (STAI Hubbulwathan Duri, 2022)
This research aims to find out the work of students as young social entrepreneurs who are supported by curriculum instruments, understand the process of students consolidating themselves as young social entrepreneurs as well as thinkers, and the emergence of new awareness among students as young social entrepreneurs figure. This research is descriptive qualitative research. Informants in the study numbered 70 students who had businesses such as culinary, service providers, fashion, and others. However, the participants who were willing to be interviewed were only 9 students. Data collection is done through interviews, then the data is analyzed through data reduction, data presentation, and conclusion drawing. The results of the study showed that there was a change in student self-orientation as an agent of change characterized by the process of consolidation into a young social entrepreneur who has the ability to find loopholes and opportunities outside of their academic tasks. The ability to do this cracking zone, actually students want to get out of their comfort zone while trying to realize new awareness to become young social entrepreneurs in the midst of uncertain social, economic, and political conditions.